HUBUNGAN LINGKAR LENGAN ATAS (LILA) DENGAN BERAT BADAN LAHIR BAYI DI PKM SEI PANAS KOTA BATAM - Potu(1), Eni; Susanti, Rini (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2017)
Maternal nutrition status of pregnancy is affected by development and fetus growth, that nutrition will consumed pregnancy mother used to fetus growth as big as 40% and for mother requirement 60%. To know the nutrition status during the pregnancy, that used is measurement on Mid Upper Arm Circumference (MUAC). The actual size of normal by mid upper arm circumference (MUAC) is ≥ 23,5 cm. MUAC to be trusted relation with the weight of newborn baby. Research intending to figure out the relation between the nutrition status of pregnant mothers based on the measurement of Mid Upper Arm Circumference (MUAC) with the wight of babies born.The methods of this research is Quantitatif  with retrospektifapproach. using secondary data and with number of the respondent is 35. Statistic test used on chi square test.The result of this research, of 35 respondents 33 mothers with MUAC  ≥ 23,5 cm (94,3%) gives birth to babies with normal birth weight of 28 babies (84,8%) and babies with large birth wight is 5 babies (15,2%). And 2 mothers with MUAC ≤ 23,5 cm (5,7%) gives birth to babies with low birth weight of 2 babies (5,7%). The result of this research used SPSS 16.0 that based on Chi-Square test is acquired a significant correlation with two variables is shown by p=0,000 (p value < 0,05).The conclusions of this research it’s means that there is a relation of nutrition status of pregnant mothers based measurement on MUAC with the weight of the baby born